FATIGUE FAILURE MECHANISM ANALYSIS OF SHEARER CUTTING GEARBOX - LI Peng (Jixie qiangdu)
Focus on fatigue fracture of shearer cutting gearbox housing（ SCGH）,the fatigue failure mechanism of（ SCGH）is investigated considering both high frequency internal excitation caused by gear meshing and low frequency external excitation caused by coal cutting. Force analysis is proposed to obtain the region of stress concentration and stress values are calculated by finite element analysis. Torque caused by gear meshing Mp and eccentric L0 is firstly considered in mechanical model and the influence of them on strain amplitude is analyzed. Local resonance characteristics are analyzed based on vibration signals of shearer cutting experiment. Power spectral density（ PSD） analysis is used to obtain local resonance frequencies and they were checked to be natural frequencies of SCGH. Based on strain modal analysis,the region of strain concentration of modal shape and stress concentration are compared. The results show that: Region of local resonance modal shape strain concentration is similar to that of stress concentration. 15th 23 th and 27th vibration modes are excited by gear meshing excitation and cause local resonance of SCGH. Beat phenomenon which accelerates fatigue fracture of SCGH is caused by close space of 23th and 27th vibration modes.Fatigue fracture failure of SCGH was caused by both stress concentration and local resonance.